Computational Fluid Dynamics Simulation of Bubble Column Reactor Hydrodynamics - Rahimi, R.; Salehi, M.A.; Nandaumar, K. (Asian Journal of Chemistry, 2010)
In this research, hydrodynamic behaviour of a bubble column reactor was determined. In previous works, the prediction of gas holdup is not accurately covered. For that reason, the turbulence in liquid phase is modelled by standard k-ε model. In addition, local axial velocity, velocity distribution and local gas hold-up were calculated by Fluent 6.0.3, which is a commercial software. The results have been compared with experimental data, which show quite a good agreement.